2006
DOI: 10.1038/nature04495
|View full text |Cite
|
Sign up to set email alerts
|

Role of genomic instability and p53 in AID-induced c-myc–Igh translocations

Abstract: Chromosomal translocations involving the immunoglobulin switch region are a hallmark feature of B-cell malignancies 1 . However, little is known about the molecular mechanism by which primary B cells acquire or guard against these lesions. Here we find that translocations between cmyc and the IgH locus (Igh) are induced in primary B cells within hours of expression of the catalytically active form of activation-induced cytidine deaminase (AID), an enzyme that deaminates cytosine to produce uracil in DNA 2,3 . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
366
1
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 321 publications
(395 citation statements)
references
References 31 publications
25
366
1
3
Order By: Relevance
“…Our results combined with previous results (Ramiro et al, 2004(Ramiro et al, , 2006Franco et al, 2006b;Dorsett et al, 2007) suggest that the primary oncogenic role of AID is to induce c-myc/IgH translocations. Another possibility is that AID does not have an impact on lymphoma development when c-myc/IgH translocation events precede AID expression.…”
Section: Reduced Rag1 Expression In B Cells Does Not Impact C-myc Lymsupporting
confidence: 71%
See 1 more Smart Citation
“…Our results combined with previous results (Ramiro et al, 2004(Ramiro et al, , 2006Franco et al, 2006b;Dorsett et al, 2007) suggest that the primary oncogenic role of AID is to induce c-myc/IgH translocations. Another possibility is that AID does not have an impact on lymphoma development when c-myc/IgH translocation events precede AID expression.…”
Section: Reduced Rag1 Expression In B Cells Does Not Impact C-myc Lymsupporting
confidence: 71%
“…AID is specifically expressed in germinal center B cells (Muramatsu et al, 2000) and initiates somatic hypermutation and class switch recombination in Ig genes by deaminating cytidines within Ig genes (reviewed in (Di Noia and Neuberger, 2007)). Numerous reports show that c-myc/IgH or bcl-2/IgH translocations are mediated by the RAG proteins (Korsmeyer, 1992;Raghavan et al, 2004) and by the AID enzyme (Ramiro et al, 2004(Ramiro et al, , 2006Franco et al, 2006b;Dorsett et al, 2007), and indeed, these enzymes have been found to mutate or cause DNA breaks outside of Ig genes (Korsmeyer, 1992;Shen et al, 1998;Muschen et al, 2000;Pasqualucci et al, 2001;Franco et al, 2006a) reinforcing the possibility that many other genes are susceptible to AID-and RAG-mediated mutations. Although RAG proteins and AID mediate chromosomal translocations, it has yet to be established whether these enzymes play additional roles in subsequent transformation events.…”
mentioning
confidence: 99%
“…Fifth, Tp53 deficiency leads to or unmasks the oncogenic potential of RAG-dependent Igh/c-myc and Tcra/c-myc translocations and AID-initiated Igh/c-myc translocations in lymphocytes lacking histone H2AX Celeste et al, 2003a;Bassing et al, 2007). Sixth, Tp53 suppresses the frequency of nonmalignant B cells with AID-initiated Igh/c-myc translocations (Ramiro et al, 2006;Santos et al, 2010). Seventh, Tp53 À/À mice with inactivation of NHEJ in mature B cells succumb to tumors with oncogenic Igh/cmyc translocations arising through CSR errors, or clonal translocations involving aberrant Igk and Igl V(D)J recombination (Wang et al, 2008(Wang et al, , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, DDR factor inactivation in mature B lymphocytes is accompanied by chromosomal translocations that occur during CSR in 53BP1 -/- [59,60] and H2AX -/-[61] mice. A very elegant recent study demonstrated that AID-induced DNA-dsb can associate to DNA-dsb generated by other experimental means, such as through IsceI endonuclease digestion, thus recapitulating the formation of a chromosomal translocation [62].…”
Section: Nhej and Csrmentioning
confidence: 99%